Integration of Transcriptome and Proteome in Lymph Nodes Reveal the Different Immune Responses to PRRSV Between PRRSV-Resistant Tongcheng Pigs and PRRSV-Susceptible Large White Pigs - Liang, Wan; Meng, Xiangge; Zhen, Yueran; Zhang, Yu; Hu, Xueying; Zhang, Qingde; Zhou, Xiang; Liu, Bang (Frontiers in Genetics, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is an infectious disease that seriously affects the swine industry worldwide. Understanding the interaction between the host immune response and PRRS virus (PRRSV) can provide insight into the PRRSV pathogenesis, as well as potential clues to control PRRSV infection. Here, we examined the transcriptome and proteome differences of lymph nodes between PRRSV-resistant Tongcheng (TC) pigs and PRRSV-susceptible Large White (LW) pigs in response to PRRSV infection. 2245 and 1839 differentially expressed genes (DEGs) were detected in TC and LW pigs upon PRRSV infection, respectively. Transcriptome analysis revealed genetic differences in antigen presentation and metabolism between TC pigs and LW pigs, which may lead to different immune responses to PRRSV infection. Furthermore, 678 and 1000 differentially expressed proteins (DEPs) were identified in TC and LW pigs, and DEPs were mainly enriched in the metabolism pathways. Integrated analysis of transcriptome and proteome datasets revealed antigen recognition capacity, immune activation, cell cycles, and cell metabolism are important for PRRSV clearance. In conclusion, this study provides important resources on transcriptomic and proteomic levels in lymph nodes for further revealing the interaction between the host immune response and PRRSV, which would give us new insight into molecular mechanisms related to genetic complexity against PRRSV.